2021
DOI: 10.21873/invivo.12510
|View full text |Cite
|
Sign up to set email alerts
|

A Gender Comparison of Bone Metabolic Changes After Gastric Cancer Surgery: A Prospective Observational Study

Abstract: Background/Aim: This study was designed to investigate gender-related differences in changes in bone metabolism after gastric cancer surgery. Patients and Methods: We prospectively recruited 47 patients (38 males and 9 females) who had early gastric cancer. The bone mineral density (BMD), serum levels of 1,25-dihydroxy vitamin D (1,25(OH) 2 VD), 25-hydroxy vitamin D (25(OH)VD), and estradiol (E2) were measured before and after surgery. Results: BMD significantly decreased 12 months after surgery by median degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…However, the findings of several authors suggest that gastric cancer gastrectomy does not affect serum vitamin D concentration levels, or at least some of its metabolites, as stated previously. A study by Atsumi et al in 2021 showed that the concentration levels of 25(OH)D, 1,25(OH) 2 D remained stable 12 months after the surgery [14]. In 2019, the same author reported that despite surgery, 1,25(OH) 2 D levels were consistently in the normal range up to two years of follow-up [17].…”
Section: Rino Y Et Al [27] 16 Patientsmentioning
confidence: 97%
See 4 more Smart Citations
“…However, the findings of several authors suggest that gastric cancer gastrectomy does not affect serum vitamin D concentration levels, or at least some of its metabolites, as stated previously. A study by Atsumi et al in 2021 showed that the concentration levels of 25(OH)D, 1,25(OH) 2 D remained stable 12 months after the surgery [14]. In 2019, the same author reported that despite surgery, 1,25(OH) 2 D levels were consistently in the normal range up to two years of follow-up [17].…”
Section: Rino Y Et Al [27] 16 Patientsmentioning
confidence: 97%
“…The first report was made by Kobayashi et al in 1994 [31], while the newest data were reported by Atsumi et al in 2021 [14]. The investigated vitamin D metabolites were 25(OH)D (11 studies) [14,[17][18][19]21,[23][24][25][26]28,31], 1,25(OH) 2 D (6 studies) [14,17,24,25,27,31], and 24,25(OH) 2 D (2 studies) [24,31]. Six studies did not report the investigated metabolite [15,16,20,22,29,30], declaring that they analyzed "serum vitamin D".…”
Section: Rino Y Et Al [27] 16 Patientsmentioning
confidence: 97%
See 3 more Smart Citations